Impact of teleoncology on the quality of life in patients after radiotherapy treatment (Research, Society and Development, 2025)
Objective: to analyze the impact of teleoncology on the quality of life of patients after radiotherapy treatment. Methodology: This is a quantitative, cohort, longitudinal and prospective research. Nursing teleconsultations were carried out for three months to monitor patients with breast cancer who had completed radiotherapy treatment, with subsequent application of a questionnaire to evaluate them. The data were analyzed with simple and descriptive statistics. Results: It was noted that radiotherapy causes significant side effects after treatment, especially skin changes, with an impact on patients' quality of life, but these tend to be minimized with time and professional monitoring, through teleconsultations. Conclusions: Therefore, teleoncology presents itself as a viable alternative for monitoring these effects, without the need for the patient to return to the service.